Editors' Choice—The Effectiveness of Multifunctional Li-Ion Battery Separators past Their Saturation with Transition Metal Ions. Issue 10 (1st January 2018) - Banerjee, Anjan; Ziv, Baruch; Luski, Shalom; Aurbach, Doron; Halalay, Ion C.
Abstract : Li-ion batteries (LIBs) for electric vehicles necessitate a 10-year useful life. The dissolution of manganese and other transition metal ions from positive electrodes, and the loss of Li + ions are two main causes for reduced LIB durability. Multifunctional separators (MFSs) designed to mitigate these degradation modes enable improvements in the electrochemical performance of LIBs at both room and above-ambient temperatures. We report herein on the benefits for the cycle life and rate performance of Lix Mn2 O4 ||graphite cells by composite MFSs that incorporate a crosslinked styrene-divinylbenzene copolymer functionalized with disodium iminodiacetate groups. Our study shows that: (1) forming effective passivating electrode surface films early in LIB life is essential for good performance and long life; (2) saturation of MFSs with manganese ions does not subsequently lead to an increased capacity loss rate during high-temperature (55°C) cycling; (3) MFSs also improve rate performance. These benefits originate from a diminished crossover of dissolved Mn ions to the negative electrode, reduced losses of electroactive Li + ions, and smaller interfacial resistances at both positive and negative electrodes.